Investigation of K-L,K-s -> pi(+)pi(-)e(+)e(-) decays - Lai, A; Marras, D; Bevan, A; Dosanjh, R; Gershon, T; Hay, B; Kalmus, G; Lazzeroni, C; Munday, D; Needham, MD; Olaiya, E; Parker, M; et al. (2003)
The KL → π+π-e +e- and KS → π+π -e+e- decay modes have been studied in detail using the NA48 detector at the CERN SPS. Based on the data collected during the 1998 and 1999 run periods, a sample of 1162 KL → π +π-e+e- candidates has been observed with an expected background level of 36.9 events, yielding the branching ratio measurement BR(KL → π+π -e+e-) = (3.08 ± 0.20) × 10 -7. The distribution of events in the sinφ cosφ variable, where φ is the angle between the π+π- and the e+e- decay planes in the kaon centre of mass, is found to exhibit a large CP-violating asymmetry with the value Aφ = (14.2 ± 3.6)%. For the KS → π+π -e+e- decay channel, 621 candidates have been identified in the 1999 data sample with an estimated background contribution of 0.7 event. The corresponding branching ratio has been determined to be BR(K S → π+π-e+e-) = (4.71 ± 0.32) × 10-5. The combined value of this measurement with the published 1998 result is BR(KS → π +π-e+e-) = (4.69 ± 0.30) × 10-5. No asymmetry is observed in this decay mode. Our results are in good agreement with theoretical predictions based on a phenomenological description of radiative kaon decays. The form factor parameters a1/a2 and g̃M1 in the K L → π+π-e+e- direct emission process as well as the value of the K0 charge radius have been extracted from the data.